Dampak Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Prima Beton Bangun Persada Gresik - Siti Khotimah; Harsono Teguh; Rina Dewi; Achmad Daengs GS; I Gd Wiyasa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
In today's increasingly advanced business world, speed and determination are the main keys to the success of every business activity. Therefore, the initial steps for every company are to know quickly and precisely what its employees want and need and what is required. expected by the company. Fulfill or provide employee needs, both in the form of motivation and facilities - facilities which will have a positive impact if they are all in accordance with business activities. Leadership style and work environment influence employee performance. Leadership style and work environment perceived by employees can improve performance or reducing employee performance. Employees who enjoy their work environment will have an impact on increasing the performance of a company, apart from that, the leadership style in the company can make employees feel comfortable, so this will also have an impact on employee performance to produce the best. This research aims to determine the influence of leadership style and work environment on employee performance. This research instrument uses a questionnaire with a total of 30 respondents. The sample taken is employees of PT Prima Beton Bangun Persada Gresik. The research method used is a quantitative method.